SPECIES COMPOSITION OF NYMPHALID BUTTERFLIES IN MAINLAND (KUBAH NATIONAL PARK) AND ISLAND (SATANG BESAR ISLAND), SARAWAK - Suraya, Shahidan; Christharina, S Gintoron; Stanly Merum, Mawar; Muhamad Ikhwan, Idris; Raziman Imam, Ghazali (Penerbit UMT, 2022)
Species diversity is a good measure of habitat quality. In order to gain this knowledge, bio-indicator species such as butterflies is among the species to be observed. In this study, nymphalids were recorded in mainland (Kubah National Park) and island (Satang Besar Island), Sarawak by using 20 baited traps in 20 days of sampling period. A total of 93 individuals representing 25 species were documented. Species diversity index was higher in the mainland (H’= 2.8639) with 87 individuals comprising 24 species. This could be due to the habitat homogeneity and thus less variety of food resources in the island. Species abundance in the mainland was dominated by the Nymphalinae (13.48%) of both Bassarona dunya and Tanaecia aruna. Meanwhile, Melanitis leda was the most abundant species recorded (67%) in the island. Mainland was more speciose in terms of butterfly composition as compared to island and distribution pattern of butterflies were also observed.